Antibacterial and Antifungal Properties of Citronella oil Against Streptococcus mutans and Candida albicans by In Vitro Study - Sugiaman, Vinna Kurniwati; Widowati, Wahyu; Widya Kusuma, Hanna Sari Widya Kusuma; Salsabila, Nindia; Rizal, Rizal (Jurnal Kedokteran Brawijaya, 2024)
Streptococcus mutans and Candida albicans are the main microorganisms that cause dental cavities. It can cause infection, damaged tissue around teeth, abscesses, and focal infection to other organs in the body. Natural products are currently widely used as products or as additives in the prevention of dental caries which have more anti-bacterial and anti-fungal activities than antibiotics that can cause resistance. Citronella (Cymbopogon citratus) is abundant and easy to grow. This study was conducted to determine the effectiveness of citronella (Cymbopogon citratus) oil on the growth of S. mutans and C. albicans microorganisms by Minimum Inhibitory Content (MIC) and Minimum Bactericidal Content (MBC). The method of MIC is broth microdilution by making chlorhexidine concentration levels of 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, and 0.2% with 4 replications each. The MIC value was determined based on absorbance spectrophotometry and the MBC value was determined from the agar plate using the spread method. Biofilm eradication test was conducted by crystal-violet staining and measuring the absorbance. The results of MIC and MBC were obtained on S. mutans, namely at concentrations of 25% and 100%, respectively. Meanwhile, the results of MIC and MBC on C. albicans were obtained at concentrations of 50% and 100%, respectively. Furthermore, the citronella oil has antibacterial and antifungal activities.